2010
DOI: 10.2310/7750.2010.09037
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Scale for Acne Scar Severity (SCAR-S) of the Face and Trunk

Abstract: SCAR-S is a practical, validated, global system for acne scar evaluation and is clinically relevant in overall severity grading of acne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 13 publications
3
40
0
3
Order By: Relevance
“…Tan et al 5 reported that the risk of acne scars increases as disease duration increases. Moreover, in the present study, patients with scars experienced more severe acne symptoms (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tan et al 5 reported that the risk of acne scars increases as disease duration increases. Moreover, in the present study, patients with scars experienced more severe acne symptoms (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous guidelines on the appropriate treatment of acne, and several methods for morphological classification of scars have been proposed. 4,5 However, no consensus has been reached with regard to the evaluation and subsequent classification of acne scars. Although Jacob et al 6 have reported on different treatment options based on acne scar morphology, there is currently no standard treatment for scarring.…”
Section: Introductionmentioning
confidence: 99%
“…[4] A larger study of 973 patients suggested that 55% of patients have clinically relevant scarring on the face, 14% scarring on the chest and 24% scarring on the back. [7] The proportion of patients with scarring in our clinic appears to be lower (43%) than previously reported, in part attributable to different populations being sampled, who may be referred to our clinic at an earlier stage, and perhaps owing to the subjective nature of scar assessment.…”
Section: Discussionmentioning
confidence: 65%
“…The acne scars were graded according to the Scale for Acne Scar Severity (SCAR-S) given by Tan and colleagues, 8 and the predominant scar type was recorded. The study protocol conformed to the ethical guidelines of the 1975 Declaration of Helsinki, and approval of the institution's research review committee was taken.…”
mentioning
confidence: 99%